KOLABORASI STAKEHOLDERS DALAM PENERAPAN MANAJEMEN MUTU TERPADU DI LEMBAGA PENDIDIKAN ISLAM - Farhan, Ach; Rijal, Syamsul (AHSANA MEDIA: Jurnal Pemikiran, Pendidikan dan Penelitian Ke-Islaman, 2025)
The quality of Islamic education is a strategic issue in facing the challenges of globalization and people's demands for quality educational services. This article discusses the implementation of Total Quality Management (TQM) as a strategy to improve the quality of education in madrasas by emphasizing the principles of customer satisfaction, continuous improvement, teamwork, and the involvement of all stakeholders. This study uses a library research approach by analyzing literature, regulations, and previous research results that are relevant to the quality management of Islamic education. The results of the study show that quality development in madrasas requires the active participation of all parties, both internally (madrasah heads, teachers, staff) and externally (parents, community, government). The implementation of TQM in Islamic education includes strengthening organizational systems, setting clear quality standards, fact-based management, and a collaborative work culture oriented towards continuous improvement. Madrasas that successfully implement the principles of TQM are able to improve the quality of learning, stakeholder satisfaction, and competitiveness of graduates. This study confirms that the success of the development of the quality of Islamic education is highly dependent on collective commitment, visionary leadership, and awareness of the importance of maintaining the relevance of education to the needs of society.